Students and language teachers attitudes and beliefs towards the learning and teaching of qualitative research: An exploratory study - Alcazaren, Holden Kenneth G. (Animo Repository, 2018)
Academic institutions in the Philippines have been integrating research into the course works of the students. By incorporating research and emphasizing its significance to how academic institutions work, teachers create graduates who are capable to think critically, to solve problem effectively and to make decisions wisely. With the Department of Educations (DepEd) Enhanced Act of 2013, schools have implemented the senior high school (SHS) curriculum which intends to cope with the global standards in terms of the country's high school graduates. In the SHS curriculum, one of the specialized subjects that is offered is the Practical Research 1 course, which focuses on qualitative research methods. As implied in the literature, it is clear that when it comes to research, students tend to view these courses negatively. In order to construct conducive learning experiences for the Practical Research 1 course, it is necessary to consider the effect of ones attitude and belief towards research, not just of student, but also, with the teachers. In this exploratory study, semi-structured interviews of 8 research teachers and a focus group discussion of 6 SHS students were conducted. They were selected from a large university in Bacoor, Cavite through purposive sampling method. Constant Comparative Method (CCM) of Glaser and Strauss (1967) were used to analyze and to code interview transcripts. Using Biggs 3P model (1989; 2003), findings were categorized into presage, process and product factors. It is revealed that teachers who handle the class perceive themselves as having limited knowledge and mastery towards the subject due to the fact that they had limited exposure to research, specifically qualitative research, during their pre-service programs. Moreover, students have pointed out how their various learning experiences had become advantageous or hindrance in learning of research. It is also discovered that majority of the class activities were lecture-type discussions that were perceived as boring and insufficient by the students. However, when it comes to the outcomes of the subject, it is evident that both the teachers and students recognize the significance of the subject towards ones academic and professional endeavors. With these findings, various improvements should be implemented for the SHS curriculum to be successful in the future.